2018
DOI: 10.1177/1533034618765254
|View full text |Cite
|
Sign up to set email alerts
|

DCE-MRI-Derived Volume Transfer Constant (Ktrans) and DWI Apparent Diffusion Coefficient as Predictive Markers of Short- and Long-Term Efficacy of Chemoradiotherapy in Patients With Esophageal Cancer

Abstract: This study aimed to evaluate both the short- and long-term efficacies of chemoradiotherapy in relation to the treatment of esophageal cancer . This was achieved through the use of dynamic contrast-enhanced magnetic resonance imaging–derived volume transfer constant and diffusion weighted imaging–derived apparent diffusion coefficient . Patients with esophageal cancer were assigned into the sensitive and resistant groups based on respective efficacies in chemoradiotherapy. Dynamic contrast-enhanced magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Moreover, higher pre-ktrans in the HIF-1α(À) may reflect a better treatment response compared with the HIF-1α(+), according to the above early response evaluation and previous studies. 35 Inevitably, there were several limitations in this study. First, the sample size was relatively small, and a larger sample is necessary in further studies.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, higher pre-ktrans in the HIF-1α(À) may reflect a better treatment response compared with the HIF-1α(+), according to the above early response evaluation and previous studies. 35 Inevitably, there were several limitations in this study. First, the sample size was relatively small, and a larger sample is necessary in further studies.…”
Section: Discussionmentioning
confidence: 91%
“…EC is a common digestive tract cancer that occurs among the elderly, with the mortality rate of EC in China being the highest in the world. Chemotherapy is the first choice for the treatment of EC ( 22 ). However, many factors may impact the therapeutic effects of chemotherapy drugs, such as the p53 background and the efficiency of drug delivery ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ADC has the potential value in early predicting or evaluating the therapeutic effect of CRT for esophageal cancer. 4 - 6 This study was designed to investigate the value of ADC in early predicting or evaluating the therapeutic effect of CRT for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%